The Influence of Price, Promotion and Product Warranty on Purchasing Decisions for Second Cellphones at Bless Phone Solo - Setiawan, Andreas; Handaruwati, Indah (Universitas Kristen Immanuel, 2025)
The use of smartphones is increasing in various circles which makes demand continue to rise and provides opportunities for the cellphone buying and selling business, many things influence purchasing decisions for a product. This study aims to analyze the effect of price, promotion and product warranty on purchasing decisions for second handphones. This type of research is quantitative research with a total sample in this study of 40 people selected based on non-probability sampling techniques (not random) with purposive sampling sample selection techniques, namely respondents who have bought second handphone products at Bless Phone Solo and are at least 17 years old and the data collection method uses a questionnaire. The results showed that the price variable had no partial effect on purchasing decisions, the promotion variable had a partial effect on purchasing decisions and the product warranty had a partial effect on purchasing decisions. These three independent variables simultaneously influence the decision to purchase a second cellphone at Bless Phone Solo.